MicroRNA-mediated dysregulation of neural developmental genes in HPRT deficiency: clues for Lesch–Nyhan disease? - Guibinga, Ghiabe-Henri (Oxford University Press, 2012)
Mutations in the gene encoding the purine biosynthetic enzyme hypoxanthine–guanine phosphoribosyltransferase (HPRT) cause the intractable neurodevelopmental Lesch–Nyhan disease (LND) associated with aberrant development of brain dopamine pathways. In the current study, we have identified an increased expression of the microRNA miR181a in HPRT-deficient human dopaminergic SH-SY5Y neuroblastoma cells. Among the genes potentially regulated by miR181a are several known to be required for neural development, including Engrailed1 (En1), Engrailed2 (En2), Lmx1a and Brn2. We demonstrate that these genes are down-regulated in HPRT-deficient SH-SY5Y cells and that over-expression of miR181a significantly reduces endogenous expression of these genes and inhibits translation of luciferase plasmids bearing the En1/2 or Lmx1a 3′UTR miRNA-binding elements. Conversely, inhibition of miR181a increases the expression of these genes and enhances translation of luciferase constructs bearing the En1/2 and Lmx1a 3′UTR miRNA-binding sequences. We also demonstrate that key neurodevelopmental genes (e.g. Nurr1, Pitx3, Wnt1 and Mash1) known to be functional partners of Lmx1a and Brn2 are also markedly down-regulated in SH-SY5Y cells over-expressing miR181a and in HPRT-deficient cells. Our findings in SH-SY5Y cells demonstrate that HPRT deficiency is accompanied by dysregulation of some of the important pathways that regulate the development of dopaminergic neurons and dopamine pathways and that this defect is associated with and possibly due at least partly to aberrant expression of miR181a. Because aberrant expression of miR181a is not as apparent in HPRT-deficient LND fibroblasts, the relevance of the SH-SY5Y neuroblastoma cells to human disease remains to be proven. Nevertheless, we propose that these pleiotropic neurodevelopment effects of miR181a may play a role in the pathogenesis of LND.